Perancangan Fasilitas Kerja Pada Bagian Staffing/Packing Dengan Pendekatan Ergonomi Untuk Mengurangi Risiko Musculoskeletal Disorder (MSDS): Studi Kasus Di PT Excellence Qualities Yarn (PT EQY) - Septia Nur Safitri; Anita Oktaviana Trisna Devi; Bekti Nugrahadi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT EQY is a textile company, especially yarn spinning. The activities of the staffing/packing department at PT EQY are packing, lifting, and moving cardboard boxes. This activity still relies on human power or manual material handling. This work is carried out repeatedly and continuously, causing complaints of pain in several parts of the body during work. This raises the risk of work postures such as Musculoskeletal disorders (MSDs). This research aims to produce a design for work aids that can reduce the risk of Musculoskeletal disorders (MSDs) using the Ovako Work Analysis System (OWAS) method. Based on the problem, work posture analysis was carried out using the OWAS method to find out whether the work posture of staffing/packing employees falls into the risky posture category or not. Based on the results of the Ovako Work Analysis System (OWAS) analysis research, it shows that the posture of staffing/packing workers is included in the high risk category and needs immediate improvement. This improvement involves designing work facilities, namely a handlift and packing table with an ergonomics approach, resulting in a handlift design with a height of 200 cm (2000 mm) and a packing table with a width of 200 cm (2000 mm) and a packing table with a length of 60 cm (600mm), width 60 cm(600mm), and height 104 cm(1040mm).